Mandibular metastasis of cutaneous melanoma - Josi Amadeu; Cleto Mariosvaldo Piazzetta; Cassius Carvalho Torres-Pereira; José Miguel Amenábar (Journal of Oral Biology and Craniofacial Research)
Melanoma is a malignant neoplasm of melanocytes that can metastasize to every organ of the body, but metastasis to the oral cavity is uncommon. We describe a case of metastatic malignant melanoma to the mandible in a 33-years-old woman. The patient had a 2 cm × 4 cm firm, ulcerated nodule, distal to the second mandibular right molar. Incisional biopsy revealed epithelioid cells and immunohistochemistry was positive for HMB-45, S-100 protein and vimentin. The patient was referred to the local cancer hospital for treatment but died 3 months later. Metastatic malignant melanomas of the oral cavity are rare and unusual. Early diagnosis of the primary tumor is essential for successful treatment and to improvement of patient prognosis.